Cement cementing prepad fluid as well as preparation and application thereof
By preparing a cement cementing preliminary containing barite, suspension stabilizer, retarder, glycan and quaternary ammonium carboxylic acid, the problem of thickening after contact with the cement slurry is solved, and the problem of oil-based mud and cement slurry is improved The quality of cementing operations and the condensation performance of cement slurry achieve high temperature stability and anti-pollution effects.
Patent Information
- Application Number
- CN202411294545.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-07
AI Technical Summary
After the oil-based mud comes into direct contact with the cement slurry, it leads to dynamic migration of free water, thickening and difficult to solidify, endangering the construction safety of cementing operations, and the compressive strength of the mixed cement stone is reduced, affecting oil and gas mining and wellbore quality.
A cement cementing preliminary liquid is used, and its composition includes 70-100 parts of barite, 0.5-1.2 parts of suspension stabilizer, 1-5 parts of retarder, 4-6 parts of poly(1,4)-2- Amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkylsulfonate, 2-8 parts of quaternary ammonium carboxylic acid and 80-90 parts of water, prepared by specific formula and stirring methods, to form effective Liquid system that isolates oil-based mud and cement slurry.
It has achieved wetting and flipping, good high-temperature resistance, strong suspension stability and strong pollution resistance, improved the quality of cementing operations and the condensation performance of cementing slurry, and ensured the long-term sealing quality of the wellbore.
Smart Images

Figure BDA0005045539280000041
Abstract
Description
Technical Field
[0001] The invention relates to a cement well cementing pre-fluid and its preparation and application. Background Art
[0002] Oil-based mud is a type of drilling fluid with oil as the continuous phase. Compared with water-based drilling fluid, it has better salt and temperature resistance, excellent lubricity and stability, can effectively ensure the stability of the well wall and the protection of oil and gas reservoirs, and is widely used in the development of oil and gas in high-temperature deep wells and complex rock formations.
[0003] However, due to the different physical and chemical properties of oil-based mud and cement slurry, after the two are in direct contact, the cement slurry mixed with oil phase will undergo dynamic migration of internal free water, usually showing thickening and difficulty in solidification. As the difficulty of pumping performance increases and the setting time of cement slurry is extended to varying degrees, it not only endangers the construction of cementing operations, but also is very unsafe for subsequent oil and gas extraction and maintenance due to the reduction in the compressive strength of the mixed cement stone.
[0004] In actual cementing field construction, in order to improve the quality of cementing operations, an isolation fluid system that can effectively flush the oil-based mud residue on the well wall and efficiently isolate the contact between the two fluids is usually pumped into the well before cementing. By effectively cleaning the drilling fluid remaining in the casing and the well wall annulus, the bonding interface is improved and the quality of cementing operations is improved.
[0005] The quality of the wellbore is directly related to the success or failure of the drilling project and the life of the oil and gas well. Cementing is the key technology to ensure the quality of the well project. Cement slurry is the core technology of cementing and an important means to ensure the sustainable and high-quality development of oil and gas field exploration and development. Due to the complex geological conditions, pressure system, temperature system, well depth structure and other complex problems in ultra-deep wells, the long-term isolation quality must be guaranteed. In particular, the safety density window is narrow, and it is difficult to return the cementing once and continuously fill the cement. Under the conditions of high and low pressure coexistence, the cementing quality pass rate is low, and the performance of cement slurry needs to be further improved. Summary of the invention
[0006] In order to improve the cementing effect in deep well oil and gas development, the present invention provides a cement cementing pre-fluid, which can effectively isolate the oil-based mud and cement slurry on the well wall.
[0007] As one aspect of the present invention, it relates to a cement well cementing pre-fluid, whose components and weight percentages are as follows: 70-100 parts of barite, 0.5-1.2 parts of suspension stabilizer, 1-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
[0008] As an optimization, its components and mass proportions are as follows: 70-100 parts of barite, 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
[0009] As a further optimization, its components and mass proportions are as follows: 70-100 parts of barite, 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
[0010] As another aspect of the present invention, it relates to a method for preparing the above-mentioned cement cementing pre-fluid, comprising: adding 0.5-1.2 parts of a suspension stabilizer, 3-5 parts of a retarder, 4-6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, and 0.3-5 parts of tributyl phosphate to 80-90 parts of water, fully dissolving them, then adding 70-100 parts of a weighting material, barite, stirring and mixing, to obtain a cement cementing pre-fluid.
[0011] As an optimization, the method includes: adding 0.8-1.2 parts of suspension stabilizer GWS-100L, 4-5 parts of retarder GWR-300L, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium salt carboxylic acid, and 0.3-0.5 parts of tributyl phosphate into 80-90 parts of water, stirring to dissolve, adding 70-100 parts of weighting material barite, stirring and mixing, and obtaining cement cementing pre-fluid.
[0012] As a further optimization, the method includes: adding 0.8-1.2 parts of suspension stabilizer GWS-100L, 4-5 parts of retarder GWR-300L, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium salt carboxylic acid, and 0.3-0.5 parts of tributyl phosphate into 80-90 parts of water, stirring to dissolve, adding 80-100 parts of weighting material barite, stirring and mixing, and obtaining cement cementing pre-fluid.
[0013] As another aspect of the present invention, it relates to the application of the above-mentioned cementing pre-fluid in oil and gas development.
[0014] As another aspect of the present invention, it relates to an oil and gas development process, which uses the above-mentioned cement cementing pre-fluid.
[0015] The cement well cementing pre-fluid provided by the present invention can realize wetting reversal, can withstand high temperatures above 200° C., has good suspension stability and strong anti-pollution ability. DETAILED DESCRIPTION
[0016] Example 1:
[0017] Take 60 parts of barite, 0.3 parts of stabilizer (high viscosity carboxymethyl cellulose CMC HVT produced by Panjin Petrochemical Company of China National Petroleum Corporation Great Wall Drilling Engineering Co., Ltd.), 1 part of retarder (phosphate polymer GWR-200L for oil well cement produced by Cementing Company of China National Petroleum Corporation Great Wall Drilling Engineering Co., Ltd. in 2013), 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 2 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.3 parts of tributyl phosphate.
[0018] Put 80 parts of water into the mud mixing cup, start the motor and keep it at a speed of 2000r / min±200r / min, then evenly add 0.3 parts of high viscosity carboxymethyl cellulose CMCHVT, 1 part of phosphate polymer retarder GWR-200L, 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 2 parts of quaternary ammonium salt carboxylic acid, 0.3 parts of tributyl phosphate, continue stirring for 2 minutes until fully dissolved, then add 60 parts of weighting material barite, continue stirring at a speed of 4000r / min±200r / min for 20 minutes, stir the slurry completely evenly, and obtain cement cementing pre-fluid. After the system components are fully stirred, the performance evaluation is carried out.
[0019] The sedimentation stability test was carried out using a normal pressure viscosifier: more than 500 ml of the prepared pre-liquid was placed in a normal pressure viscosifier at an experimental temperature of 25°C and stirred for 20 minutes, then poured into a dry 500 ml measuring cylinder. After standing at room temperature for 2 hours, the mixed uniform density of the upper and lower 250 ml pre-liquids was measured according to the method specified in Chapter 6 of GB / T19139. The density difference between the upper and lower pre-liquids was calculated to be 0.6 g / cm 3 , the suspension stability performance is poor.
[0020] Compatibility test of pre-dip fluid and cement slurry was carried out using atmospheric pressure thickener: Cement slurry was prepared according to Chapter 5 of GB / T19139 Oil Well Cement Test Method. Stirred in atmospheric pressure thickener for 20 minutes, then measured the reading at a speed of 300 r / min, and the viscosity η of cement slurry was calculated. 水泥浆Measure the cement slurry and pre-liquid in a volume ratio of 75:25 as needed, prepare a uniform mixed slurry, use a mud stirring cup, stir at a speed of 4000r / min±200r / min for 60s, place it in a normal pressure thickener and stir for 20min, measure the reading at a speed of 300r / min, and calculate the viscosity η of the mixed slurry 混浆 .
[0021] Compatibility coefficient η1 (the closer the ratio is to 1, the better the compatibility)
[0022] η1=η 水泥浆 η 混浆
[0023] The final calculated compatibility coefficient η1 is 0.76, which does not meet the compatibility requirements.
[0024] The temperature resistance of the pre-pad fluid was measured using a high-temperature pressurized thickener: the pre-pad fluid was subjected to a thickening test at a test temperature of 200°C and a pressure of 100 MPa. The initial consistency was 13Bc, and when the temperature was raised to 180°C, the consistency dropped to 3Bc, indicating that the pre-pad fluid slurry was thin and could not withstand the high temperature of 180°C.
[0025] The anti-pollution performance of the pre-fluid, cement slurry and oil-based drilling fluid was experimentally determined using a high-temperature pressurized thickener: Cement slurry was prepared according to Chapter 5 of GB / T19139 Oil Well Cement Test Method. The cement slurry formula was: APIG grade oil and gas well cement + 2% G33S (BWOC, by weight of cement) + 3.5% (BWOC) microsilica, water-cement ratio 0.44; the oil-based mud sample was taken from a deep well at 2200m, with a density of 1.60g / cm 3 . Cement slurry, cement slurry, oil-based mud and pre-fluid in a volume ratio of 7:2:1 were taken as needed to mix the mixed slurry evenly, and the thickening time of cement slurry and mixed slurry were measured at a test temperature of 180°C and a pressure of 90MPa. The thickening time of cement slurry was 290min, and the thickening time of mixed slurry was 256min, which was shortened by 34min, and obvious oil invasion was observed in cement.
[0026] Wetting reversal performance test was carried out using a conductivity meter: the conductivity of the high temperature resistant oil-based mud or crude oil was calibrated, the default initial value was 0, the pre-fluid was configured according to the experimental requirements, the configured pre-fluid was dripped into the oil-based mud or crude oil, the conductivity of the mixed solution at different volume ratios was measured, and the records were made and the curves were drawn. When the volume ratio of the dripping into the crude oil exceeded 78%, wetting reversal occurred, which was lower than the required standard.
[0027] The six-speed rotary viscometer is used to test the flushing efficiency performance: the rotating outer cylinder of the rotary viscometer is removed by rotation, and its initial mass W0 is weighed. The part below the scale line of the rotating outer cylinder of the rotary viscometer is evenly coated with oil-based mud or crude oil, and the mass W1 is weighed, and the rotating outer cylinder is put back into the viscometer. The pre-liquid that has been heated and cured for 20 minutes according to the target temperature is filled into the sample cup of the rotary viscometer, and the rotary viscometer is started and rotated at a speed of 300r / min for 5 minutes. The sample rotor is taken out to drain the water, and the weight is recorded as W2, and the flushing efficiency is calculated.
[0028]
[0029] The final calculated flushing efficiency was 72%, which was considered to be unable to meet the demand.
[0030] Example 2:
[0031] Take 80 parts of barite, 0.8 parts of stabilizer (polymer JK37 produced by Sinopec Kunshan Co., Ltd.), 3 parts of phosphate polymer retarder GWR-200L, 4 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 90 parts of water, and 0.4 parts of tributyl phosphate.
[0032] 90 parts of water were added to the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 0.8 parts of polymer thickener JK37, 3 parts of phosphate polymer retarder GWR-200L, 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, and 0.4 parts of tributyl phosphate were added successively and uniformly, and stirring was continued for 2 minutes until fully dissolved, and then 90 parts of weighting material barite were added, and stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the stirring slurry was completely uniform to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0033] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3, the suspension stability is good; the compatibility coefficient with cement slurry is 0.84, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 275min, which is 15min shorter than the thickening time of cement slurry 290min, which does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 22Bc, and when the temperature is raised to 200℃, the consistency drops to 8Bc, indicating that the pre-liquid slurry is normal and can withstand high temperatures of 200℃. The conductivity measurement volume ratio exceeds 52% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 87%, and it is believed that the flushing efficiency cannot meet the requirements.
[0034] Example 3:
[0035] Take 100 parts of barite, 0.5 parts of stabilizer (HBK-3S, a biopolymer for oil well cement produced by Panjin Hongbo Petroleum Technology Service Co., Ltd.), 4 parts of phosphate polymer retarder GWR-200L, 5 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium carboxylic acid, 80 parts of water, and 0.5 parts of tributyl phosphate.
[0036] 80 parts of water were added to the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 0.5 parts of biopolymer stabilizer HBK-3S, 4 parts of phosphate polymer retarder GWR-200L, 5 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium salt carboxylic acid, and 0.5 parts of tributyl phosphate were added successively and uniformly, and stirring was continued for 2 minutes until fully dissolved, and then 100 parts of weighting material barite was added, and stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0037] The experimental results show that the density difference between the upper and lower parts after standing is 0.3g / cm 3 , the suspension stability is poor; the compatibility coefficient with cement slurry is 0.78, which does not meet the compatibility requirements; the thickening time in the anti-pollution experiment is 277min, which is 13min shorter than the thickening time of cement slurry 290min, which does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 25Bc, and when the temperature is raised to 200℃, the consistency drops to 8Bc, indicating that the pre-liquid slurry is normal but cannot withstand the high temperature of 200℃; the conductivity measurement volume ratio exceeds 44% and wetting reversal occurs, which meets the required standards; the flushing efficiency is 95%, and the flushing efficiency meets the requirements.
[0038] Example 4:
[0039] Take 100 parts of barite, 0.5 parts of isolation fluid additive (GWY-100S, a heat-resistant bio-adhesive and fatty alcohol ether launched in 2014 by the Cementing Company of China National Petroleum Corporation Great Wall Drilling Engineering Co., Ltd.), 5 parts of retarder (HBH-100L, an organic phosphate for oil well cement produced by Panjin Hongbo Petroleum Technology Service Co., Ltd.), 6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 8 parts of quaternary ammonium carboxylic acid, 90 parts of water, and 0.3 parts of tributyl phosphate.
[0040] 90 parts of water were put into the mud mixing cup, and the motor was started and maintained at a speed of 2000r / min±200r / min. 0.5 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 5 parts of organic phosphate retarder HBH-100L, 6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 8 parts of quaternary ammonium salt carboxylic acid, 0.3 parts of tributyl phosphate were added successively and uniformly, and then stirred for 2 minutes until fully dissolved, and then 100 parts of weighting material barite were added, and stirred at a speed of 4000r / min±200r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0041] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.82, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 325min, which is 35min longer than the thickening time of cement slurry 290min, which meets the standard requirements; in the temperature resistance performance measurement, the initial consistency is 22Bc, and when the temperature is raised to 200℃, the consistency drops to 5Bc, indicating that the pre-liquid slurry is normal but cannot withstand the high temperature of 200℃; the conductivity measurement volume ratio exceeds 52% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 96%, and the flushing efficiency meets the requirements.
[0042] Example 5:
[0043] Take 80 parts of barite, 1 part of high viscosity carboxymethyl cellulose CMC HVT, 1 part of retarder (phosphate polymer GWR-300L for oil well cement launched in 2017 by Cementing Company of China National Petroleum Corporation Great Wall Drilling Engineering Co., Ltd.), 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 2 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.4 parts of tributyl phosphate.
[0044] 80 parts of water were added to the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 1 part of high viscosity carboxymethyl cellulose CMC HVT, 1 part of phosphate polymer retarder GWR-300L, 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 2 parts of quaternary ammonium salt carboxylic acid, and 0.4 parts of tributyl phosphate were added in succession and uniformly, and then 80 parts of weighting material barite were added, and the stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0045] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.80, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 254min, which is 36min shorter than the thickening time of cement slurry 290min, and does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 25Bc, and when the temperature is raised to 200℃, the consistency drops to 4Bc, indicating that the pre-liquid slurry is normal but cannot withstand the high temperature of 200℃; the conductivity measurement volume ratio exceeds 54% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 75%, and it is believed that the flushing efficiency cannot meet the demand.
[0046] Example 6:
[0047] Take 70 parts of barite, 1 part of emulsifier (fatty acid derivative emulsifier GWFAD (Type II) produced by Panjin Petrochemical Company of China National Petroleum Corporation Great Wall Drilling Engineering Co., Ltd.), 3 parts of phosphate polymer retarder GWR-300L, 5 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.5 parts of tributyl phosphate.
[0048] 80 parts of water were added to the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 1 part of fatty acid derivative emulsifier GWFAD (type II), 3 parts of phosphate polymer retarder GWR-300L, 5 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 0.5 parts of tributyl phosphate were added in succession and uniformly, and then 60 parts of weighting material barite were added, and the stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the stirring slurry was completely uniform to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0049] The experimental results show that the density difference between the upper and lower parts after standing is 0.1g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.74, which does not meet the compatibility requirements; the thickening time in the anti-pollution experiment is 275min, which is 15min shorter than the thickening time of cement slurry 290min, and does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 25Bc, and when the temperature is raised to 200℃, the consistency drops to 12Bc, indicating that the pre-liquid slurry is normal and can withstand high temperatures of 200℃; the conductivity measurement volume ratio exceeds 46% and wetting reversal occurs, which meets the required standards; the flushing efficiency is 86%, and it is believed that the flushing efficiency cannot meet the needs.
[0050] Example 7:
[0051] Take 80 parts of barite, 0.8 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 5 parts of phosphate polymer retarder GWR-200L, 4 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium salt carboxylic acid, 90 parts of water, and 0.3 parts of tributyl phosphate.
[0052] 90 parts of water were added into the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 0.8 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 5 parts of phosphate polymer retarder GWR-200L, 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium salt carboxylic acid, 0.3 parts of tributyl phosphate were added successively and uniformly, and then stirred for 2 minutes until fully dissolved, and then 80 parts of weighting material barite were added, and stirred at a speed of 4000 r / min±200 r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0053] The experimental results show that the density difference between the upper and lower parts after standing is 0.1g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.77, which does not meet the compatibility requirements; the thickening time in the anti-pollution experiment is 305min, which is 15min longer than the thickening time of cement slurry 290min, which meets the standard requirements; in the temperature resistance performance measurement, the initial consistency is 22Bc, and when the temperature is raised to 200℃, the consistency drops to 9Bc, indicating that the pre-liquid slurry is normal and can withstand high temperatures of 200℃; the conductivity measurement volume ratio exceeds 52% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 92%, and the flushing efficiency meets the requirements.
[0054] Example 8:
[0055] Take 100 parts of barite, 0.8 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 4 parts of organic phosphate retarder HBH-100L, 4 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 8 parts of quaternary ammonium salt carboxylic acid, 90 parts of water, and 0.4 parts of tributyl phosphate.
[0056] 90 parts of water were put into the mud mixing cup, and the motor was started and maintained at a speed of 2000r / min±200r / min. 0.8 parts of heat-resistant bio-gum and fatty alcohol ether cementing spacer fluid additive GWY-100S, 4 parts of organic phosphate retarder HBH-100L, 4 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8 parts of sodium alkyl sulfonate, 8 parts of quaternary ammonium salt carboxylic acid, 0.4 parts of tributyl phosphate were added successively and uniformly, and the mixture was stirred for 2 minutes until fully dissolved, and then 100 parts of weighting material barite were added, and the mixture was stirred for 20 minutes at a speed of 4000r / min±200r / min until the slurry was completely uniform, and the cement cementing pre-fluid was obtained. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0057] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3, the suspension stability is good; the compatibility coefficient with cement slurry is 0.80, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 280min, which is 10min shorter than the thickening time of cement slurry 290min, and does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 24Bc, and when the temperature is raised to 200℃, the consistency drops to 15Bc, indicating that the pre-liquid slurry is relatively viscous but can withstand high temperatures of 200℃; the conductivity measurement volume ratio exceeds 50% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 94%, and the flushing efficiency meets the requirements.
[0058] Example 9:
[0059] Take 100 parts of barite, 1.2 parts of biopolymer stabilizer HBK-3S, 4 parts of phosphate polymer retarder GWR-300L, 6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 3 parts of quaternary ammonium salt carboxylic acid, 90 parts of water, and 0.5 parts of tributyl phosphate.
[0060] 90 parts of water were added into the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 1.2 parts of biopolymer stabilizer HBK-3S, 4 parts of phosphate polymer retarder GWR-300L, 6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 2 parts of quaternary ammonium salt carboxylic acid, and 0.5 parts of tributyl phosphate were added successively and uniformly, and stirring was continued for 2 minutes until fully dissolved, and then 100 parts of weighting material barite was added, and stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0061] The experimental results show that the density difference between the upper and lower parts after standing is 0.1g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.80, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 288min, which is 2min shorter than the thickening time of cement slurry 290min, and does not meet the standard requirements; in the temperature resistance performance measurement, the initial consistency is 37Bc, and when the temperature is raised to 200℃, the consistency drops to 25Bc, indicating that the pre-liquid slurry is very viscous and can withstand high temperatures of 200℃; the conductivity measurement volume ratio exceeds 66% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 88%, and it is believed that the flushing efficiency cannot meet the needs.
[0062] Example 10:
[0063] Take 80 parts of barite, 1.2 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 5 parts of phosphate polymer retarder GWR-200L, 6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.3 parts of tributyl phosphate.
[0064] 80 parts of water were put into the mud mixing cup, and the motor was started and maintained at a speed of 2000r / min±200r / min. 1.2 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 5 parts of phosphate polymer retarder GWR-200L, 6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 6 parts of quaternary ammonium salt carboxylic acid, 0.3 parts of tributyl phosphate were added successively and uniformly, and then stirred for 2 minutes until fully dissolved, and then 80 parts of weighting material barite were added, and stirred at a speed of 4000r / min±200r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0065] The experimental results show that the density difference between the upper and lower parts after standing is 0.1g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.88, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 318min, which is 28min longer than the thickening time of cement slurry 290min, which meets the standard requirements; in the temperature resistance performance measurement, the initial consistency is 32Bc, and when the temperature is raised to 200℃, the consistency drops to 26Bc, indicating that the pre-liquid slurry is normal and can withstand high temperature of 200℃; the conductivity measurement volume ratio exceeds 44% and wetting reversal occurs, which meets the required standards; the flushing efficiency is 92%, and the flushing efficiency meets the requirements.
[0066] Example 11:
[0067] Take 70 parts of barite, 0.8 parts of biopolymer stabilizer HBK-3S, 5 parts of phosphate polymer retarder GWR-300L, 5 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.4 parts of tributyl phosphate.
[0068] 80 parts of water were added to the mud mixing cup, and the motor was started and maintained at a speed of 2000 r / min±200 r / min. 0.8 parts of biopolymer stabilizer HBK-3S, 5 parts of phosphate polymer retarder GWR-300L, 5 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 12 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, and 0.4 parts of tributyl phosphate were added successively and uniformly, and stirring was continued for 2 minutes until fully dissolved, and then 60 parts of weighting material barite were added, and stirring was continued at a speed of 4000 r / min±200 r / min for 20 minutes, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0069] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.76, which does not meet the compatibility requirements; the thickening time in the anti-pollution experiment is 312min, which is 22min longer than the thickening time of cement slurry 290min, which meets the standard requirements; in the temperature resistance performance measurement, the initial consistency is 21Bc, and when the temperature is raised to 200℃, the consistency drops to 14Bc, indicating that the pre-liquid slurry is thin and cannot withstand the high temperature of 200℃; the conductivity measurement volume ratio exceeds 52% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 90%, and the flushing efficiency meets the requirements.
[0070] Example 12:
[0071] Take 100 parts of barite, 0.8 parts of heat-resistant bio-glue and fatty alcohol ether cementing spacer fluid additive GWY-100S, 4 parts of phosphate polymer retarder GWR-300L, 6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 80 parts of water, and 0.5 parts of tributyl phosphate.
[0072] 80 parts of water were put into the mud mixing cup, and the motor was started and maintained at a speed of 2000r / min±200r / min. 0.8 parts of heat-resistant bio-gum and fatty alcohol ether cementing spacer fluid additive GWY-100S, 4 parts of phosphate polymer retarder GWR-300L, 6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 10 parts of sodium alkyl sulfonate, 4 parts of quaternary ammonium salt carboxylic acid, 0.5 parts of tributyl phosphate were added successively and uniformly, and then stirred for 2 minutes until fully dissolved, and then 100 parts of weighting material barite were added, and stirred for 20 minutes at a speed of 4000r / min±200r / min, and the slurry was stirred completely uniformly to obtain cement cementing pre-fluid. After the system components were fully stirred, the performance evaluation of the above example 1 was carried out.
[0073] The experimental results show that the density difference between the upper and lower parts after standing is 0.2g / cm 3 , the suspension stability is good; the compatibility coefficient with cement slurry is 0.85, which meets the compatibility requirements; the thickening time in the anti-pollution experiment is 300min, which is 10min longer than the thickening time of cement slurry 290min, which meets the standard requirements; in the temperature resistance performance measurement, the initial consistency is 19Bc, and when the temperature is raised to 200℃, the consistency drops to 16Bc, indicating that the pre-liquid slurry is normal and can withstand high temperature of 200℃; the conductivity measurement volume ratio exceeds 48% and wetting reversal occurs, which is lower than the required standard; the flushing efficiency is 95%, and the flushing efficiency meets the requirements.
[0074] It can be seen from the above examples that the static upper and lower density differences of the pre-fluids obtained in Examples 2-12 are relatively small, that is, when the formula meets the following conditions and the following preparation method is used, the suspension stability of the pre-fluid is good.
[0075] Formula: 70-100 parts of barite, 0.5-1.2 parts of biopolymer or heat-resistant bioadhesive and fatty alcohol ether stabilizer, 1-5 parts of phosphate polymer retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, 0.3-0.5 parts of tributyl phosphate.
[0076] Preparation method: 0.5-1.2 parts of biopolymer or heat-resistant bio-gum and fatty alcohol ether stabilizer, 3-5 parts of phosphate polymer, 4-6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, 0.3-5 parts of tributyl phosphate are added successively to 80-90 parts of water, and the mixture is fully dissolved. Then, 70-100 parts of weighting material barite are added, and the mixture is stirred and mixed to obtain cement cementing pre-fluid.
[0077] Furthermore, from the comparison of the above embodiments, it can be seen that in the temperature resistance test of Examples 6-12, the consistency drop in the thickening experiment is relatively low, that is, when the formulation conditions meet the following conditions and the following preparation method is adopted, the temperature resistance is better.
[0078] Formula: 70-100 parts of barite, 0.8-1.2 parts of heat-resistant bio-gum and fatty alcohol ether, 4-5 parts of phosphate polymer, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium carboxylic acid, 80-90 parts of water, 0.3-0.5 parts of tributyl phosphate.
[0079] Preparation method: 0.8-1.2 parts of heat-resistant bio-gum and fatty alcohol ether, 4-5 parts of phosphate polymer, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium salt carboxylic acid, 0.3-0.5 parts of tributyl phosphate are successively added into 80-90 parts of water, stirred to dissolve, 70-100 parts of weighting material barite are added, stirred and mixed to obtain cement cementing pre-flushing fluid.
[0080] Furthermore, from the comparison of the above examples, it can be seen that the anti-pollution experiments of Examples 7, 10-12 show that the thickening time is longer than that of cement slurry. When the formula meets the following conditions and the following preparation method is adopted, the suspension stability, temperature resistance and anti-pollution effect of the pre-fluid are relatively good.
[0081] Formula: 70-100 parts of barite, 0.8-1.2 parts of heat-resistant bio-gum and fatty alcohol ether, 4-5 parts of phosphate polymer, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium carboxylic acid, 80-90 parts of water, 0.3-0.5 parts of tributyl phosphate.
[0082] Preparation method: 0.8-1.2 parts of heat-resistant bio-gum and fatty alcohol ether, 4-5 parts of phosphate polymer, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium salt carboxylic acid, 0.3-0.5 parts of tributyl phosphate are successively added into 80-90 parts of water, stirred to dissolve, 80-100 parts of weighting material barite are added, stirred and mixed to obtain cement cementing pre-fluid.
Claims
1. A cementing pre-fluid, characterized in that: Its components and mass proportions are as follows: 70-100 parts of barite, 0.5-1.2 parts of suspension stabilizer, 1-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
2. The cementing pre-fluid according to claim 1, characterized in that: Its components and mass proportions are as follows: 70-100 parts of barite, 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
3. The cementing pre-fluid according to claim 2, characterized in that: Its components and mass proportions are as follows: 70-100 parts of barite, 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium salt carboxylic acid, 80-90 parts of water, and 0.3-0.5 parts of tributyl phosphate.
4. The cementing pre-fluid according to any one of claims 1 to 3, characterized in that: The suspension stabilizer is a biopolymer or a temperature-resistant bio-glue and a fatty alcohol ether.
5. The cementing pre-fluid according to any one of claims 1 to 3, characterized in that: The retarder is a phosphate polymer retarder.
6. A method for preparing the cementing pre-fluid according to claim 1, characterized in that: include: In 80-90 parts of water, add 0.5-1.2 parts of suspension stabilizer, 3-5 parts of retarder, 4-6 parts of poly (1,4)-2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 2-8 parts of quaternary ammonium salt carboxylic acid, and 0.3-5 parts of tributyl phosphate successively, fully dissolve, then add 70-100 parts of weighting material barite, stir and mix well to obtain cement cementing pre-fluid.
7. A method for preparing the cementing pre-fluid according to claim 2, characterized in that: include: 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 3-8 parts of quaternary ammonium salt carboxylic acid, 0.3-0.5 parts of tributyl phosphate are added successively into 80-90 parts of water, stirred to dissolve, 70-100 parts of weighting material barite are added, stirred and mixed to obtain cement cementing pre-fluid.
8. A method for preparing the cementing pre-fluid according to claim 3, characterized in that: include: 0.8-1.2 parts of suspension stabilizer, 4-5 parts of retarder, 4-6 parts of poly (1, 4) -2-amino-2-deoxy-β-D-glucose, 8-12 parts of sodium alkyl sulfonate, 4-6 parts of quaternary ammonium salt carboxylic acid, 0.3-0.5 parts of tributyl phosphate are added successively into 80-90 parts of water, stirred to dissolve, 80-100 parts of weighting material barite are added, stirred and mixed to obtain cement cementing pre-fluid.
9. Use of the cement well-cementing pre-fluid according to any one of claims 1 to 5 in oil and gas development.
10. An oil and gas development process, characterized in that: Use the cement well cementing pre-fluid described in any one of claims 1-5.